Improving Students’ Reading Skill Of Narrative Text By Using Authentic Materials - Putri Selvina Panjaitan (Jurnal Ilmiah Mahasiswa Pendidikan [JIMEDU], 2022)
This research was aimed to describe the improvement of the students’ reading skill on narrative text by using Authentic Material. The subject of this research was the IX grade students of SMP Muhammadiyah 08 Medan in the Academic Year 2018/2019 with 41 students. It was conducted by using classroom action research. The instruments of collecting the data were observation sheet, interview,and tests which were carried out in two cycles and the two cycles conducted in sixmeetings. The tests were given to the students in the form of pre-test, post test I in the first cycle, and post test II in the second cycle. The technique of analyzingdata applied quantitative and qualitative research. The result of data analysis showed that there was an improvement on the students’ reading on narrative text from each cycle. It was showed from the mean of pre-test which was 50.97. After Authentic Material was applied in the first cycle, there was an improvement of the result of the students’ mean which was 62.68 and for the second cycle after reflection on the first cycle, there was an improvement of students’ mean which was 84.63. Moreover, pre-test there was 4.87% (2 students) who got over 70. In post test I in the first cycle there was 34.15% (14 students) who got over 70. In post test II in the second cycle there was 100% (41 students) who got over 70. In other words, the students’ reading on narrative text was improved and based on the interview, and the observation sheet, they showed that students motivation andenthusiastic were also improved.